Obesity in Libya: a review - Rafik R. Elmehdawi (Libyan Journal of Medicine, 2012)
Obesity is a global epidemic resulting in major morbidity and premature death. About 64% of Libyan adults are either overweight or obese, obesity progressively increasing with age, and two times more common among Libyan women than men. Cases of obesity and overweight are increasing in Libya as well as all over the world, with genetic and environmental factors playing a contributory role. With its known significant morbidity and mortality, obesity should draw the attention of the healthcare community, researchers, and policy makers in Libya.